Morpho-agronomıc varıabılıty, herıtabılıty and genetıc advance studıes ın sesame (sesamum ındıcum L.) In nıgerıa (Bangladesh Journal of Botany, 2024)
The study explored morpho-agronomic and biochemical traits to assess variability level and the degree of genetic diversity in 15 Sesame accessions. Data were subjected to analysis of variance, multivariate analyses, and genetic parameters were estimated. Significant differences (P < 0.05) existed among the accessions in all the characters. Four components with a cumulative variation of 85.7% were extracted. Substantial broad sense heritability estimates and high genetic gain were observed in secondary branches (97.8%; 719.4%), primary branches (96.1%;142,5%), capsules per plant (97.8%; 141.1%), single plant seed yield (86.87%; 46.03%), capsule length (99.16%; 32%), and 500 seed weight (95.15%; 34.12%). It may be inferred that a considerable level of variability existed among the accessions studied and charcters like branching habit, capsules per plant, capsule length and single plant seed yield  could be considered for selection in breeding for superior genotypes.Bangladesh J. Bot. 53(1): 75-81, 2024 (March)